Los incentivos laborales y su influencia en el rendimiento de los colaboradores del centro de contacto del Banco de Crédito del Perú sucursal La Esperanza 2016 - Rodríguez Aliaga, Deysi Karina (2017)
The present research aims to propose an incentive program for the collaborators of the contact center of the Bank of Credit of Peru branch La Esperanza, with the purpose of improving the performance of the mimes, to contribute to the growth of the organization. The research problem is related to the following question: How do the labor incentives influence the performance of the collaborators of the contact center of the Bank of Credit of Peru branch La Esperanza: 2016 ?, whose hypothesis is: Job incentives influence Significantly improving the performance of the collaborators of the contact center of the BCP La Esperanza branch. Emphasis as variables of independent variable study: Job Incentives, dependent variable: The performance of the collaborators of the contact center of the Bank of Credit of Peru branch La Esperanza: 2016. The study population consisted of 40 workers, the sample was represented by the same workers, the data collection technique was applied to the survey. Through the results obtained it can be seen that the workers consider that the incentives will positively influence their performance, they like the idea of implementing additional incentives to improve their performance. The incentives they would most like to be given to workers are the compliance bonus, welfare incentives, recreational activities, and recognition of accomplishments. It is recommended to the center of the Bank of Credit of Peru branch La Esperanza, adopt the proposal of the incentive program to improve the performance of its workers reaching the proposed objectives and exceed the performance standards.